Pengembangan Gateway untuk Menghubungkan Jaringan IoT (Internet Of Things) Dan Jaringan Blockchain - Muhammad Chalif Nurfaizi; Adhitya Bhawiyuga; Kasyful Amron (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The large amount of data generated from Internet of Things (IoT) devices makes cloud computing widely used as IoT data storage. Cloud computing which has full access control over IoT data, causes a limitation where users are unable to fully manage and monitor the data they have. Users also can not know the integrity of each data. Therefore, we need a system that can store IoT data while also giving users more access control in managing and monitoring their data. On the other hand, blockchain, a technology with a decentralized architecture that has a consensus mechanism, is able to guarantee the integrity of any data stored without centralized authority. With these advantages, it is expected that the blockchain can become an alternative solution in managing and storing IoT data. In this study, the integration between the Internet of Things and the blockchain is to develop a gateway as an intermediary in terms of sending sensor data. The results of this study is gateway is able to receive data from sensor nodes, manage data structures and send them to the blockchain network. In addition, the authentication mechanism was also successfully provided in order to validate the gateway as a form of limiting access to the blockchain network. Finally, the measurement of gateway performance gives a success rate of 100% and an average processing time of 0.52 ms.